2020
DOI: 10.4193/rhin19.258
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of endoscopic partial middleturbinectomy surgery on the quality of life of patients with chronic rhinosinusitis and nasal polyps

Abstract: Background: Chronic rhinosinusitis (CRS) is a common chronic inflammatory disease. Endoscopic sinus surgery is recommended as a standard method when medical treatment fails. The effectiveness of various complementary surgical methods such as endoscopic partial middle-turbinectomy is controversial in the improvement of CRS symptoms in these patients. This study aimed to investigate the effect of endoscopic partial middle-turbinectomy on the quality of life (QOL) of patients with chronic rhinosinusitis and nasal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Although the original descriptions of the Messerklinger technique stressed tissue preservation and a “functional” approach, some surgeons advocate varying degrees of middle nasal concha resection as a matter of routine practice, and clinical investigations report few problems. (Dayal et al, 2016; Delarestaghi et al, 2020; Akiyama et al, 2018; Tomoum et al, 2021; Pinther et al, 2019.) Each time the surgeon resects a middle nasal concha and the patient does not experience a complication, it reinforces the practice as safe in the mind of the surgeon.…”
Section: Review/discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although the original descriptions of the Messerklinger technique stressed tissue preservation and a “functional” approach, some surgeons advocate varying degrees of middle nasal concha resection as a matter of routine practice, and clinical investigations report few problems. (Dayal et al, 2016; Delarestaghi et al, 2020; Akiyama et al, 2018; Tomoum et al, 2021; Pinther et al, 2019.) Each time the surgeon resects a middle nasal concha and the patient does not experience a complication, it reinforces the practice as safe in the mind of the surgeon.…”
Section: Review/discussionmentioning
confidence: 96%
“…This reasoning would translate into tens of thousands of healthy middle turbinates resected annually. (Rice et al, 2003)In an effort to avoid total resection of the middle nasal concha and limit resection of olfactory tissue, rhinologic surgeons have developed and advocated limited middle turbinectomy techniques, for example, partial middle turbinectomy that limits resection to the lower bulbous portion of the concha while preserving the lamellar portion with its superior and posterior extension/element (Delarestaghi et al, 2020). Others have developed and advocated submucosal resection of the lower bulbous portion, removing only the bone element while preserving the submucosa and mucosal tissue to preserve olfactory function, mucoiliary clearance and humidification (Akiyama et al).…”
Section: Review/discussionmentioning
confidence: 99%
“…26 Another research by Delarestaghi et al, suggested that the addition of partial middle-turbinectomy in endoscopic sinus surgery improves QOL of patients. 27 de Carvalho et al evaluated olfactory loss in patients who underwent expanded endoscopic approach with partial middle turbinectomy and NSF reconstruction and they found that the deterioration in the sense of smell was transient up to 3 months. 28 Several studies utilized the SNOT-22 to evaluate QOL in patients operated for pituitary lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ESS can be extended by aggressive removal of all sinus mucosa (so-called "reboot surgery"). As neatly summarized in EPOS2020, a debate is ongoing on the needed extent of surgery and as yet, no firm conclusions can be drawn on the added value of more aggressive approaches (18)(19)(20).…”
Section: Appropriate Medical Therapy and Fess; Limitations In N-erdmentioning
confidence: 99%